Damage detection techniques for wind turbine blades: A review. (July 2020) - Du, Ying; Zhou, Shengxi; Jing, Xingjian; Peng, Yeping; Wu, Hongkun; Kwok, Ngaiming
Highlights: Damage detection techniques for wind turbine blades are reviewed. Detection principles, development methods, pros and cons of each technique are addressed. Discussions on fault indicators for the aforementioned methods are presented. Research prospects on damage detection techniques for wind turbine blades are given. Abstract: Blades play a vital role in wind turbine system performances. However, they are susceptible to damage arising from complex and irregular loading or even cause catastrophic collapse, and they are expensive to maintain. Defects or damages on wind turbine blades (WTBs) not only reduce the lifespan and power generation efficiency of the wind turbine, but also increase monitoring errors, safety risks and maintenance costs. Therefore, damage detection for WTBs is of great importance for failure avoidance, maintenance planning, and operation sustainability of wind turbines. This paper provides a comprehensive review of state-of-the-art damage detection techniques for WTBs, including most of those updated methods based on strain measurement, acoustic emission, ultrasound, vibration, thermography and machine vision. Firstly, typical damages of WTBs are comprehensively introduced. Secondly, detection principles, development methods, pros and cons of the aforementioned techniques for blade inspection, and their fault indicators are reviewed. Finally, potential research directions of WTB damage detection techniques are addressed via a comparative analysis, and conclusions are drawn. It is expected that this review will provide guidelines for practical WTB inspections, as well as research prospects for damage detection techniques.